2000
DOI: 10.1038/71163
|View full text |Cite
|
Sign up to set email alerts
|

A cultural effect on brain function

Abstract: We present behavioral and anatomical evidence for a multi-component reading system in which different components are differentially weighted depending on culture-specific demands of orthography. Italian orthography is consistent, enabling reliable conversion of graphemes to phonemes to yield correct pronunciation of the word. English orthography is inconsistent, complicating mapping of letters to word sounds. In behavioral studies, Italian students showed faster word and non-word reading than English students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
383
7
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(442 citation statements)
references
References 29 publications
41
383
7
11
Order By: Relevance
“…This pattern could represent an assembled phonology (GPC) pathway that is particularly activated by nonwords. Indeed, activation of this region by nonwords relative to words in a few prior studies has been so interpreted (Mechelli et al, 2003;Paulesu et al, 2000;Xu et al, 2001). While this interpretation cannot be entirely discounted, the same pattern of activation across contrasts occurred in the left FEF and right IPS, neither of which showed differences between Regular and Irregular words.…”
Section: The Dexclusivet Dual-route Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…This pattern could represent an assembled phonology (GPC) pathway that is particularly activated by nonwords. Indeed, activation of this region by nonwords relative to words in a few prior studies has been so interpreted (Mechelli et al, 2003;Paulesu et al, 2000;Xu et al, 2001). While this interpretation cannot be entirely discounted, the same pattern of activation across contrasts occurred in the left FEF and right IPS, neither of which showed differences between Regular and Irregular words.…”
Section: The Dexclusivet Dual-route Modelmentioning
confidence: 97%
“…One relatively reliable finding is stronger activation to nonwords than words in the left frontal operculum and adjacent anterior insula (Fiez et al, 1999;Hagoort et al, 1999;Herbster et al, 1997;Mechelli et al, 2003;Paulesu et al, 2000;Xu et al, 2001). Because the dual-route model proposes greater reliance on the nonlexical GPC system in the case of nonwords, these findings have often been interpreted as evidence for such a system in the left inferior frontal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Activation in this region can be identified merely by contrasting word reading relative to rest, either with PET or with fMRI (Beauregard et al, 1997;Brunswick et al, 1999;Fiez et al, 1999;Paulesu et al, 2000;Wagner et al, 1998). This region appears as a likely source of electrical and magnetic fields that are recorded over the left ventral occipitotemporal region, with a latency of about 150 -200 ms, whenever subjects see words Cohen et al, 2000;Nobre et al, 1994;Salmelin et al, 1996;Simos et al, 2002;Tarkiainen et al, 1999).…”
Section: Evidence For Reproducible Localizationmentioning
confidence: 99%
“…Boatman et al (1997) have reported in five patients that the stimulation of one temporal electrode in this region elicited a deficit in syllable discrimination. The more posterior part of the temporal region is also activated when phonological representations are accessed through devices other than auditory input, such as lip reading (Calvert and Campbell, 2003;Calvert et al, 1997), word generation (Buchsbaum et al, 2001;Wise et al, 2001), sign language processing (Petitto et al, 2000), and reading (Paulesu et al, 2000(Paulesu et al, , 2001. It is possible that top-down attention amplifies those speech representation, thus bringing knowledge of the characteristics of a human voice to supplement the poverty of the sinewave input and integrate its acoustical features into phonemic representations.…”
Section: Fmrimentioning
confidence: 99%